Representation of Contemporary Arabic in the Film Al Rawabi School for Girls - Mujiba Sakila Irawan; Muhammad Taufiq (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This study to describe the representation of contemporary Arabic used in the dialogues of the film Al Rawabi School for Girls, given that communication is currently undergoing rapid development, particularly with the mass media serving as a communication channel. Today, the mass media has become an essential means of accessing information. The analysis focuses on how contemporary Arabic is represented in the film as the language used by characters or the narrator, without comparing it to other language varieties. The data collection techniques used are documentation and note-taking. The data analysis method employs qualitative descriptive analysis. The subject of the study consists of the dialogues or narration found in the film Al Rawabi School for Girls, specifically the use of contemporary Arabic as presented in the film. The research findings reveal that: (1) the Arabic language in this series exhibits a mixed linguistic style, blending formal Arabic (Fusha) and non-formal Arabic (‘Amiyah); (2) The language used in this series tends to be easily understood by the audience, especially by learners of Arabic; (3) This film not only depicts the social reality of adolescents but also serves as a representation of the development of contemporary Arabic in modern audiovisual media.